2021
DOI: 10.3390/cells10061300
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a New Transcriptional Co-Regulator of STEAP1 in Ewing’s Sarcoma

Abstract: Ewing’s sarcoma (ES) is caused by a chromosomal translocation leading to the formation of the fused EWSFLI1 gene, which codes for an aberrant transcription factor EWSFLI1. The transcriptional targets of EWSFLI1 have been viewed as promising and novel drug targets in the treatment of ES. One such target is six transmembrane epithelial antigen of the prostate 1 (STEAP1), a transmembrane protein that is upregulated by EWSFLI1 in ES. STEAP1 is a hallmark of tumor invasiveness and an indicator of tumor responsivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…STEAP1 is expressed in ~90% of prostate cancers and in sizeable subpopulations of other cancer types such as pancreatic cancer, glioblastoma, lung cancer, bladder cancer, breast cancer, ovarian cancer, leukemia, lymphoma, and head and neck cancer [ 14 , 15 , 20 , 21 ]. Furthermore, a key oncogenic driver in pediatric Ewing’s sarcoma is a chromosomal translocation giving the fused EWSFLI1 gene, which leads to the upregulation of STEAP1 [ 14 , 15 , 16 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…STEAP1 is expressed in ~90% of prostate cancers and in sizeable subpopulations of other cancer types such as pancreatic cancer, glioblastoma, lung cancer, bladder cancer, breast cancer, ovarian cancer, leukemia, lymphoma, and head and neck cancer [ 14 , 15 , 20 , 21 ]. Furthermore, a key oncogenic driver in pediatric Ewing’s sarcoma is a chromosomal translocation giving the fused EWSFLI1 gene, which leads to the upregulation of STEAP1 [ 14 , 15 , 16 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to EWS::FLI1, NKX2.2 is a positive regulator of STEAP1 expression ( 35 ). Initially, the transcriptional repressive roles of NKX2.2 were recognized as being necessary and sufficient for the oncogenic properties of EWS ( 36 ).…”
Section: Molecular Mechanisms and Functions Of Steap1mentioning
confidence: 99%
“…Follow-up studies found that NKX2.2-repressed genes are enriched in the EWSR1-FLI1-repressed dataset that contributes to mesenchymal differentiation and terminal differentiation [ 63 , 92 ]. More recently, studies found that NKX2.2 binds to the promoter region of STEAP1 (six transmembrane epithelial antigen of the prostate 1), a gene which is essential for EwS survival [ 94 ], together with EWSR1-FLI1 to regulate expression of STEAP1 [ 95 ]. Although this study did not highlight the direct interaction between NKX2.2 and EWSR1-FLI1 on the chromatin in the genome-wide level, it provided some understanding of how NKX2.2 coordinates the effects of EWSR1-FLI1.…”
Section: The Transcriptional Regulation Mediated By Ewsr1-fli1mentioning
confidence: 99%